A room-temperature four-terminal spin field effect transistor. (June 2021) - Liu, Jia; Peng, Zhisheng; Cai, Jinzhong; Yue, Junyi; Wei, Haonan; Impundu, Julienne; Liu, Hui; Jin, Jiyou; Yang, Zhu; Chu, Weiguo; Li, Yong Jun; Wang, Gongtang; et al.
Abstract: In analogy to the central role of transistors in conventional electronics, a key device in spintronics, spin field effect transistor (spin FET), has been predicted theoretically. Several approaches have been explored, but their applications remain a considerable challenge due to the small spin signals and low working temperature. In this work, we report a four-terminal spin FET using an individual SWNT with two partially open segments and the working mechanisms is closely related to the magnetic moments at these segments. The spin-related signals ( R spin ) can be as large as several hundred Ohm and the spin FET works at room temperature under atmospheric conditions. R spin can be modulated with gate voltages and external magnetic fields. The realization of spin FET may lead to the development of integrated circuit of spintronics, which is fundamentally different from charge-based conventional electronics. Graphical Abstract: ga1 Highlights: Room-temperature ferromagnetic semiconductor: semiconducting SWNT with open segments. Pure spin current induced by a conventional charge current in a fully separated path. Spin FET working at room temperature under atmospheric conditions. Ohmic contact between SWNT and Mo is an efficient spin injector/detector. R spin can be modulated with gate voltages and external magnetic fields.